2021
DOI: 10.3389/fphar.2021.665387
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Anticancer Agent Dimethoxycurcumin: Aspects of Pharmacokinetics, Efficacy, Mechanism, and Nanoformulation for Drug Delivery

Abstract: Curcumin is a well-known anticancer natural product with various significant bioactivities that has been well documented, but its widespread use is mainly hindered by insufficient ADME properties such as poor solubility and low metabolic stability. Dimethoxycurcumin (DiMC) is a kind of lipophilic compound derived from curcumin that maintains its anticancer potency and has greatly improved systematic bioavailability. Therefore, DiMC is regarded as a promising plant-derived anticancer agent that deserves to be w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Herein the two drug molecules involved were DOX and DiMC, a chemotherapeutic agent for various malignancies that can cause cell necrosis and apoptosis by interacting with DNA intercalation and inhibiting RNA transcription, and a promising naturally derived multifunctional anti-cancer agent, respectively (Sohail et al., 2021a ; 2021b ). It is well-known that combination therapy using drugs with different mechanisms can be synergistic, additive or antagonistic in therapeutic effects, depending greatly on the compatibility ratio of drugs (Pritchard et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein the two drug molecules involved were DOX and DiMC, a chemotherapeutic agent for various malignancies that can cause cell necrosis and apoptosis by interacting with DNA intercalation and inhibiting RNA transcription, and a promising naturally derived multifunctional anti-cancer agent, respectively (Sohail et al., 2021a ; 2021b ). It is well-known that combination therapy using drugs with different mechanisms can be synergistic, additive or antagonistic in therapeutic effects, depending greatly on the compatibility ratio of drugs (Pritchard et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the lipophilic DiMC could be entrapped into the inner hydrophobic core of the micelles through strong hydrophobic interaction during amphiphilic self-assembly. Meanwhile, the acidic hydroxyl group in DiMC from keto-enol tautomerism (Sohail et al., 2021a ; Jayakumar et al, 2016 ) could lead to efficient interaction with DOX via its basic amino group ( Figure 4C ). In view of this, DiMC could be regarded as a vital link that significantly improved the interactions among the copolymer and both drugs, therefore resulting in high encapsulation yields of CPM-DD, particularly a remarkable increase in the encapsulation efficiency of DOX.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a methylated analog of curcumin (13,15), dimethoxycurcumin (DiMC) is more metabolically stable, has better bioavailability, and exerts greater antioxidant (16) and anti-inflammatory properties (17) than does curcumin. Here, we determined effects of DiMC on the entry of SARS-CoV-2 pseudo-virus and found that DiMC blocked the entry of SARS-CoV-2 pseudo-virus in Calu-3 human non-small cell lung adenocarcinoma cells and Vero E6 green monkey kidney epithelial cells, acidified lysosomes, enhanced lysosome degradation capabilities, and promoted lysosome degradation of ACE2 as well as pseudo-SARS-CoV-2 and the SARS-CoV-2 S1 protein.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, there are some obstacles to the clinical application of curcumin, such as its low water solubility (about 11 ng mL −1 ), poor absorption, and instability. 4,5 Preclinical and clinical studies indicate the poor absorption of CCM following oral administration. Therefore, finding a method to solve this problem could be helpful in the future progress of cancer treatments through oral administration.…”
Section: Introductionmentioning
confidence: 99%